Impact of native spray-dried lactic acid bacteria, packing density and wilting time on fermentation characteristics of experimental maize and lucerne silages - Blajman, Jesica; Signorini Porchiett, Marcelo Lisandro; Vinderola, Celso Gabriel; Lingua, Mariana Soledad; Romero, Luis Alberto; Paez, Roxana Beatriz; Casas, Cecilia I.; Bergamini, Carina Viviana; Gimenez, Paula; Gaggiotti, Monica Del Carmen (Wiley, 2022)
This study aimed at investigating the effects of an autochthonous microbial inoculant microencapsulated by spray-drying on fermentation parameters, microbiological composition, mycotoxin level and aerobic stability of maize and lucerne silages. Experiment 1, a completely randomized design with a 2 × 2 × 4 factorial arrangement of treatments, evaluated inoculation (control or Lactobacillus plantarum Hv75, Pediococcus acidilactici 3903 and Lactobacillus buchneri B463), packing density (148.5 kg dry matter (DM)/m3 or 181.5 kg DM/m3) and storage period (0, 1, 30 or 60 days) in maize silage. Lactic acid bacteria (LAB) supplementation produced higher DM and lower acetic acid and deoxynivalenol contents compared to the control (p < 0.05). However, these differences were small in terms of practical applications. Experiment 2 evaluated effects of microbial inoculation (similar as in experiment 1), wilting time (3 or 21 h) and storage period (0, 3, 30 or 60 days) in lucerne silage. LAB supplementation increased DM and lactic acid content, reduced pH and concentrations of acetic acid, ethanol and ammonia nitrogen/total nitrogen compared to the control (p < 0.05). In addition, inoculation increased total LAB population and decreased yeast and mould counts (p < 0.05). Although the strains displayed potential to be used as a bio-inoculant at different lucerne moisture levels, prolonged wilting positively influenced DM, crude protein and fibre degradation (p < 0.05). Therefore, the addition of this spray-dried inoculant to lucerne silages with longer wilting could be recommended for the attainment of silage quality.